2020
DOI: 10.1017/jmech.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Density-Driven Convection in Laminated Heterogeneous Porous Media

Abstract: In the present study, we use direct numerical simulation to investigate the density-driven convection in a two-dimensional anisotropic heterogeneous porous media associated with significant laminated formation. At first, the heterogeneous porous media are randomly generated to represent laminated structure, in which the horizontal correlation length of permeability field is much longer than the vertical counterpart. Then, a highly accurate pseudo-spectral method and compact finite difference scheme with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The properties of the aquifers used are listed in the supporting information in Table S2 . [28][29][30][31], a uniform and isotropic porous medium is chosen, so as to exclude effects of heterogeneity or anisotropy on the results of the flow and mixing dynamics, and to provide a benchmark for future studies. The study is performed with a two-dimensional system to extend previous analyses reported in the literature that discusses the dissolution flux in detail but lacks a systematic evaluation of the macroscopic mixing behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the aquifers used are listed in the supporting information in Table S2 . [28][29][30][31], a uniform and isotropic porous medium is chosen, so as to exclude effects of heterogeneity or anisotropy on the results of the flow and mixing dynamics, and to provide a benchmark for future studies. The study is performed with a two-dimensional system to extend previous analyses reported in the literature that discusses the dissolution flux in detail but lacks a systematic evaluation of the macroscopic mixing behaviour.…”
Section: Introductionmentioning
confidence: 99%